(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
The main direction of the neonatology service is medical and diagnostic assistance. The training of highly qualified specialists, the effective organization of neonatal services and the availability of modern equipment make it possible to qualitatively help critically ill newborn children. The purpose of the study: to analyze the work of the department of intensive care and neonatal resuscitation of the Samarkand regional multidisciplinary Center for the period from 2017 to 2021. The research material was the annual reporting data of this department for 2017-2021. For the period from 2017 to 2021. 3666 newborns were admitted to the department, of which 589 (16%) and 3074 (84%) were admitted to the surgical department for somatic diseases, 3123 (85%) newborns were admitted from the districts of the Samarkand region, 537 (15%) from the city of Samarkand and 635 (17.3%) from other regions. High qualification of doctors, good diagnostics ensured timely resuscitation, respiratory support for newborns, correction of hemodynamic disorders, infusion therapy of newborns. But despite the intensive therapy carried out, neonatal mortality averages 10%, which poses new challenges for improving neonatal care. Thus, intensive care in neonatal intensive care is one of the main links in the provision of medical care to newborns, which requires a high level of knowledge from our doctors, the use of modern diagnostic methods, treatment that comply with state protocols.